Travel Patterns and Transportational Challenges Perceived By Older People and People Living with Disabilities in Sri Lanka - Tennekoon, V.; Wickramasinghe, R.; Peiris-John, R.; Daskon, L.; Attanayake, S.; Bandara, S.; Ameratunga, S. (My University, 2015)
Introduction - Transportation is one of the most complex and hazardous challenges faced by older people and disabled individuals that can limit their opportunities for meaningful participation in society. These vulnerable groups are also at increased risk of road traffic injuries, a public health problem disproportionately borne by people living in low and middle income countries. The objective of this study was to identify travel patterns and road traffic injury risks among older and disabled people in the Moneragala district of Sri Lanka. Moneragala, one of the largest districts in the country, is undergoing several changes designed to make the community age- and disable-friendly. Methods - Utilising a sampling frame of lists maintained by the social services department, a random household travel survey (180 households) was conducted to recruit 90 people aged over 60 years (defined as 'older people' for this study) and 90 disabled people aged five years or older (with a variety of physical and sensory impairments). All participants completed an interviewer administered questionnaire designed to identify travel patterns, perceived risks and barriers to travelling in the community. Results - The commonest modes of transportation used by older people were the public bus, walking and hired three-wheeled vehicles. Places frequently visited by older people were the hospital, temple, Sunday fair, community hall and bank. Key barriers to travel were reported as poor road conditions, lack of a disability-friendly transportation system, reckless driving and negative attitudes of the wider community. Disabled people found accessibility to public places a major barrier. Conclusions - Based on experiences reported by older people in this middle-income country, opportunities to enhance their social participation and foster their resilience would require greater attention to improving road conditions, providing accessible modes of transportation, strategies reducing risky driving by motorists, and nurturing positive societal attitudes towards more vulnerable communities.